13th International IEEE Conference on Intelligent Transportation Systems 2010
DOI: 10.1109/itsc.2010.5625071
|View full text |Cite
|
Sign up to set email alerts
|

Integration of renewable energy generation with EV charging strategies to optimize grid load balancing

Abstract: In this paper we will discuss three different Electric Vehicle Charging Strategies known as Dumb Charge, Smart Charge and Vehicle To Grid (V2G); as well as their impacts on the Portuguese Electric Transmission Grid for a 100% Electric Vehicle Fleet scenario. The future interaction between V2G and the large-scale penetration Renewable Resources will also be analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…In [19], an EV charging scheduling scheme is designed to optimize power network performance by minimizing power generation cost and power loss. In [14], three EV charging strategies, known as Dumb Charge, Smart Charge and Vehicle To Grid (V2G), are discussed, and it is found that Smart Charge is necessary to prevent large peak demand on the grid by moving EV charging to more favorable hours of energy availability and transmission grid availability.…”
Section: Related Workmentioning
confidence: 99%
“…In [19], an EV charging scheduling scheme is designed to optimize power network performance by minimizing power generation cost and power loss. In [14], three EV charging strategies, known as Dumb Charge, Smart Charge and Vehicle To Grid (V2G), are discussed, and it is found that Smart Charge is necessary to prevent large peak demand on the grid by moving EV charging to more favorable hours of energy availability and transmission grid availability.…”
Section: Related Workmentioning
confidence: 99%
“…Despite these problems, nowadays, the uncontrolled way is the most common charging procedure. As predicted in [31], in Portugal, the smart charging (in controlled way) will be a necessity in midterm, in order to prevent a large demand of energy peaks over the power grid.…”
Section: Batteries Charging Processmentioning
confidence: 99%
“…This is the most common charge procedure. As presented in [23] for the Portuguese case, in medium term, the smart charge will be necessary in order to prevent a large peak of energy demand from the electrical power grid.…”
Section: Charging Processmentioning
confidence: 99%